2016
DOI: 10.21100/msor.v14i3.307
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Tutors for Mathematics Learning Support

Abstract: This paper reports on a Mathematics Learning Support (MLS) tutor training programme implemented on a coordinated basis across three universities in Ireland in 2015 by the Irish Mathematics Learning Support Network (IMLSN). The training events were conducted in September near the start of the first semester of the academic year. Focus groups were conducted at the end of the semester in the three institutions with tutors who had participated in the training events to evaluate the workshops and their impact on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The training followed that of the previously piloted one-day four-workshop model. Forty-two tutors from six HEIs participated (Fitzmaurice et al, 2016). In September 2016, the training was offered again in a similar format and advertised across the IMLSN membership.…”
Section: Case Study 2: Training Staff Who Work In Mls In Irelandmentioning
confidence: 99%
See 2 more Smart Citations
“…The training followed that of the previously piloted one-day four-workshop model. Forty-two tutors from six HEIs participated (Fitzmaurice et al, 2016). In September 2016, the training was offered again in a similar format and advertised across the IMLSN membership.…”
Section: Case Study 2: Training Staff Who Work In Mls In Irelandmentioning
confidence: 99%
“…Within Ireland, focus groups were conducted with postgraduates 10 weeks after the September 2015 training programme. Full details of the results of these are available in Fitzmaurice et al (2016) but some of their key insights follow here. Tutors reported that the training programme was beneficial for their tutoring practice, and many recommended making it compulsory.…”
Section: Impact Of Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Through sigma a national and collaborative model for training postgraduate students has been established (Croft & Grove, 2016), and it is evident from this survey that postgraduates have a crucial role in the delivery of mathematics and statistics support provision. Further, this model of postgraduate support developed by sigma has been adopted and adapted within Ireland for use across all institutions who offer mathematics and statistics support (Fitzmaurice et al, 2016).…”
Section: Professional Development and Recognitionmentioning
confidence: 99%
“…The talk ended with an open question for the community to discuss: "having seen individuals' progress to academic careers after working in the MLSC, are these two linked, and is this of further interest and worthy of study?" Fitzmaurice et al (2016).…”
Section: Keynote Speakersmentioning
confidence: 99%